Філософія антикризового розвитку реального сектору економіки за умов глобалізації - Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Ortina, Hanna (My University, 2018)
UK: У статті наведено та обґрунтовано практичні пропозицій щодо вдосконалення державної політики розвитку реального сектору економіки за рахунок розробки першочергових антикризових заходів щодо стабілізації ситуації в країні. Встановлено, що вичікувальна антикризова політика є не прийнятною для нашої країни, оскільки вона лише виснажує ресурси країни, посилює руйнування національної господарської системи. Обґрунтовано шляхи подолання економічної кризи, які пов’язані з удосконаленням правової, соціальної, інвестиційної політики держави. Запропоновано нову модель антикризового розвитку економіки, суть якої полягає у формуванні нових пріоритетів забезпечення стійкого рівноважного економічного розвитку на засадах динамічно збалансованої економіки, які сприятимуть стійкому розвитку реального сектору економіки. EN: The article presents and substantiates practical proposals for the improvement of the state policy of development of the real sector of the economy through the development of the first-rate anti-crisis measures to stabilize the situation in the country. It has been established that the anticipating anti-crisis policy is not acceptable to our country, because it only exhausts the resources of the country, increases the destruction of the national economic system. The ways of overcoming the economic crisis that are connected with the improvement of the legal, social, investment policy of the state are substantiated. A new model of anti-crisis economic development is proposed, the essence of which is the formation of new priorities for ensuring sustainable equilibrium economic development on the basis of a dynamically balanced economy that will contribute to the sustainable development of the real sector of the economy.
Philosophy of anti-crisis development of the real economy sector under globalization conditions
Keywords: суспільство; креативність; ефективна економка; державна політика; реальний сектор економіки; глобалізація; society; creativity; efficient housekeeper; state policy; real economy; globalization